Analisis Akad Ijarah Pada Sistem Kerja Platform Digital: Perspektif Fiqih Kontemporer - Al Maghfuri, Rahmah Salsabila; Yazid, Muhammad (Rashid : Journal of Economic, 2025)
This study aims to analyze the implementation of the ijarah contract in the working system of digital platforms from a contemporary Islamic jurisprudence perspective. The research method used is a qualitative method with a literature study approach that examines classical sources, contemporary fatwas, and modern research related to the digital economy. The results show that digital platforms such as Gojek still fulfill the main elements of the ijarah contract, namely clarity of benefits (manfa'ah), clarity of ujrah, and clarity of implementation time that are clearly displayed in the application. The click mechanism in the application is considered a valid form of digital ijab and qabul as long as it demonstrates the willingness of both parties. In addition, an automatic, algorithm-based tariff calculation system can increase transparency, although dynamic tariff changes have the potential to create elements of gharar if not clearly regulated. The division of commissions between the platform and the worker partner based on a certain percentage is also acceptable in contemporary Islamic jurisprudence as long as it is agreed upon from the start and does not harm either party